Bioenergy and land use change—state of the art. Issue 3 (19th July 2012) - Berndes, Göran; Ahlgren, Serina; Börjesson, Pål; Cowie, Annette L.
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>